(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Introduction Dyslipidemia is the most common risk factor for cardiovascular morbidity and mortality worldwide requiring lifelong therapy. Hence cost of drugs plays an important role in patient’s care necessitating the need for all physicians to keep themselves updated regarding latest prices and price variation of various brands of hypolipidemic drugs. Materials and Methods Cost of oral hypolipidemic drugs manufactured by different pharmaceutical companies in the same strength and dosage forms was obtained from “Current Index of Medical Specialties” (CIMS) April- July 2017. The difference in the maximum and minimum price of the same drug manufactured by different pharmaceutical companies and percentage variation in cost per 10 tablets was calculated. Results In this study, there exists a wide cost variation among the different brands of same hypolipidemic drug. Percentage cost variation for individual hypolipidemic drugs was found to be highest with atorvastatin (20 mg FC-tablet): 1017.79% followed by rosuvastatin (20mg tablet): 308.16%, gemfibrozil (300mg capsule): 109.14%, lovastatin (20mg tablet): 87.83%, fenofibrate (200mg capsule): 79.53%, simvastatin (5mg tablet): 77.43%, ezetimibe (10mg tablet): 72.84%. Among the fixed dose combination therapy, percentage cost variation was found to be highest with atorvastatin + fenofibrate (10mg + 160mg FC-tablet): 266.67% followed by atorvastatin +ezetimibe (10mg + 10mg tablet): 139.39%, rosuvastatin + fenofibrate (10mg + 160mg tablet): 81.05% Conclusion In Indian market, there exists a wide cost variation amongst various brands of oral hypolipidemic drugs of same strength and dosage forms. Therefore, physicians should be encouraged to prescribe the drugs by generic names as they are cheaper and in no way inferior to costlier branded counterpart. This in turn reduces the economic burden on the patients.